Beginning ASP.NET 2.0 in VB 2005 - MacDonald, Matthew (Apress, 2012)
ASP (Active Server Pages) is a web development technology that's leapt through several stages of evolution. It was first introduced as an easy way to add dynamic content to ordinary web pages. Since then, it’s grown into something much more ambitious: a platformfor creating advanced web applications, including e-commerce shops, data-driven portal sites, and just about anything else you can find on the Internet. ASP.NET 2.0 is the latest version of ASP, and it represents the most dramatic change yet. With ASP.NET, developers no longer need to paste together a jumble of HTML and script code in order to program the Web. Instead, you can create full-scale web applications using nothing but code and a design tool such as Visual Studio 2005. The cost of all this innovation is the learning curve. Not only do you need to learn how to use an advanced design tool (Visual Studio) and a toolkit of objects (the .NET Framework), you also need to master a programming language such as Visual Basic 2005.